The Combined Efficacy of a Two-Year Period of Cybernic Treatment With a Wearable Cyborg Hybrid-Assistive Limb and Leuprorelin Therapy in a Patient With Spinal and Bulbar Muscular Atrophy: A Case Report - Nakatsuji, Hideaki; Ikeda, Tetsuhiko; Hashizume, Atsushi; Katsuno, Masahisa; Sobue, Gen; Nakajima, Takashi (Frontiers in Neurology, 2022)
Spinal and bulbar muscular atrophy (SBMA), also known as Kennedy’s disease, is a rare, slowly progressive, incurable, and hereditary neurodegenerative disease caused by the testosterone-dependent accumulation of pathogenic polyglutamine-expanded androgen receptor protein. After extensive review, two treatments for SBMA were recently approved in Japan; this decision was based on the results of randomized controlled trials. First, anti-androgen therapy using leuprorelin acetate (leuprorelin), a disease-modifying drug that can inhibit the progression of dysphagia but has not yet been proven to improve gait function. Second, cybernic treatment with a wearable cyborg hybrid assistive limb (HAL®) (Cyberdyne Inc. Tsukuba, Japan). The HAL is an innovative walking exercise system that has been shown to significantly improve gait function in eight neuromuscular diseases without reduction in muscle function, including SBMA. It is possible that the combination of these two approaches might yield better outcomes. However, the long-term effects of such a combined approach have yet to be clinically evaluated. Here, we describe the case of a 39-year-old male with SBMA who commenced anti-androgen therapy with leuprorelin 1 year previously; this was followed by cybernic treatment with HAL. The duration of walking exercise with HAL was 20–30 min a day in one session. Over 2 weeks, the patient underwent nine sessions (one course). The efficacy of HAL was evaluated by gait function tests before and after one course of cybernic treatment. Then, leuprorelin treatment was combined with cybernic sessions every 2 months for 2 years (13 courses in total). Walking ability, as evaluated by the 2-min walk test, improved by 20.3% in the first course and peaked 10 months after the commencement of combined therapy (a 59.0% improvement). Walking function was maintained throughout the period. Generally, SBMA is characterized by moderately increased serum levels of creatine kinase (CK), reflecting neuromuscular damage; interestingly, the patient’s CK levels decreased dramatically with combined therapy, indicating remarkable functional improvement. Long-term combined therapy improved the patient’s gait function with a steady reduction in CK levels. The combination of leuprorelin with cybernic treatment can therefore improve and maintain gait function without damaging the motor unit and may also suppress disease progression.